Understanding the Complex Work of Aboriginal Education Workers in Schools - Price, Anne; Jackson-Barrett, Elizabeth; Gower, Graeme; Herrington, Jan (The Australian Journal of Indigenous Education, 2019)
The work of Aboriginal Education Workers (AEWs) in Australian schools is complex and multifaceted, and yet it is often misunderstood, or worse, devalued. Added to this, the conditions of employment for many AEWs is often insecure, with minimal pay, few opportunities for career progression or meaningful professional development. Despite this there continues to be, as there have been for decades, research findings, policies and reports attesting to the invaluable role of AEWs in schools and communities. The theoretical standpoint of Nakata's (2007) ‘cultural interface’ is used in this paper to critically (re) examine the role of AEWs in Australian schools. Drawing from relevant past and contemporary literature, this paper draws attention to past and contemporary theorising and policy concerning the roles of AEWs. It asserts that if the work of AEWs is to be better understood and valued then it must be reconsidered in a more transformative way that benefits both the students and schools which they support.